DEVELOPMENT OF THE METHOD OF EXPERIMENTAL RESEARCH OF THE PROCESS OF EXTRACTING OIL FROM GRAPE SEEDS - Toyirov Muhriddin Zoir o’g’li (Scholar Express Journals, 2023)
The quality of life, as an integral indicator of physical, emotional and social well-being, decreases in patients with viral (HCV) liver damage already in the early stages of the disease. The most acceptable questionnaire for assessing the quality of life (QoL) in patients with viral (HCV) liver cirrhosis (LC) is the SF-36 questionnaire. According to a meta-analysis of 15 studies, in patients with chronic hepatitis C using the SF-36 questionnaire, there was a decrease in QoL compared with a healthy control group: the integral mental health component by 12.8; integral physical component of health — by 6.6 [1]. Researchers report conflicting data on the factors affecting QoL in patients with LC in the outcome of viral hepatitis C. Thus, it was found that the determining parameters of QoL are the stage of LC, age, female sex, low socioeconomic status, and marital status [2–5]. Other studies emphasize that only the stage of cirrhosis was a significant factor that reduces QoL [6]. At the same time, there are not enough studies devoted to the study of the influence of individual LC syndromes and, in particular, hepatic encephalopathy (HE) on the quality of life of patients in this category
Keywords: grape seed; grape oil; process; device